Did Mexico lose the fight of tomatoe exports in the times of USA tariff, facing the UMSCA? - Estrada Chavira, María Eugenia; Guerrero Sylja, Viridiana; Hernández Velázquez, Maribel Rocío; Arredondo Villanueva, Guillermo (2021)
U.S.A. placed in 2019, a tariff of 17.5 % in all the imports that U.S.A. made from Mexico. This tariff affected Mexican tomato growers and the Mexican export and therefore the Mexican economy. It can be said that the compensatory quotas are responsible for curbing or discouraging an unfair practice in foreign trade by charging tariffs that apply to goods imported under conditions of price discrimination or a subsidy in the country of origin, which are considered unfair practices, all this as established in the Foreign Trade Law.